Disappeared - Book 1 - Stork, Francisco X. (New York, New York : Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
Four months ago Sara Zapatas best friend, Linda, disappeared from the streets of Juarez, and ever since Sara has been using her job as a reporter to draw attention to the girls who have been kidnapped by the criminals who control the city, but now she and her family are being threatened--meanwhile her younger brother, Emiliano, is being lured into the narcotics business by the promise of big money, and soon the only way for both of them to escape is to risk the dangerous trek across the desert to the United States border.
When Sara uses her job as a reporter to draw attention to the girls who have been kidnapped, she becomes a target; meanwhile her brother Emiliano finds himself being lured into the narcotics business by the promise of big money.
HL710
Accelerated Reader
Keywords: Brothers and sisters -- Mexico; Ciudad Juz; Juvenile fiction; Women -- Violence against -- Mexico; Ciudad Juz; Juvenile fiction; Crime -- Mexico; Ciudad Juz; Juvenile fiction; Kidnapping -- Mexico; Ciudad Juz; Juvenile fiction; Reporters and reporting -- Mexico; Ciudad Juz; Juvenile fiction; Brothers and sisters -- Fiction; Kidnapping -- Fiction; Reporters and reporting -- Fiction; Brothers and sisters -- Fiction; Kidnapping -- Fiction; Reporters and reporting -- Fiction; Ciudad Juz (Mexico); Juvenile fiction; Mexico -- Fiction; Ciudad Juz (Mexico) -- Fiction; Mexico -- Fiction